1996
DOI: 10.1152/ajpheart.1996.271.3.h984
|View full text |Cite
|
Sign up to set email alerts
|

Perfusion-induced changes in cardiac O2 consumption and contractility are based on different mechanisms

Abstract: Increased cardiac perfusion results in increased oxygen consumption (VO2) and increased contractility (Gregg phenomenon) in the isolated heart. We investigated whether these two aspects of the Gregg phenomenon are related to coronary flow or arterial pressure. Coronary flow and, thus, arterial pressure were changed in the reference state and during vasoconstriction (3 nM vasopressin) in the Langendorff-perfused rat heart contracting isovolumically (ventricular balloon) at 27 degrees C (n = 5). All hearts showe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
25
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(30 citation statements)
references
References 0 publications
5
25
0
Order By: Relevance
“…Perfusion-induced changes. In our isolated perfused papillary muscles, where autoregulation is restricted due to adenosine addition, an increase in coronary perfusion pressure results in an increase in F dev , the Gregg effect, and is in line with earlier findings (13,16,36). From the literature it is known that in perfused papillary muscles an increase in oxygen delivery is not responsible (17,36).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Perfusion-induced changes. In our isolated perfused papillary muscles, where autoregulation is restricted due to adenosine addition, an increase in coronary perfusion pressure results in an increase in F dev , the Gregg effect, and is in line with earlier findings (13,16,36). From the literature it is known that in perfused papillary muscles an increase in oxygen delivery is not responsible (17,36).…”
Section: Discussionsupporting
confidence: 93%
“…The membrane deformation changes ion fluxes through SACs, resulting in increased cardiac contractility. This hypothesis is supported by the findings that the Gregg response was related to capillary perfusion (13,15) and changes in coronary vascular volume (3), but was not related to arterial endothelium or its released inotropic substances (12,14,32,33). The identity of the coronary perfusion-induced increased cation influx is not yet clear and needs further experiments.…”
Section: Discussionmentioning
confidence: 80%
“…From the literature, it is known that SACs could be located on the sarcolemma or t-tubular system of the cardiomyocytes (45); however, SACs have also been found on the vascular (33) or endocardial (24,27) endothelium. Dijkman et al (16)(17)(18) showed that perfusion-induced changes in contractility were related to Fig. 2.…”
Section: Discussionmentioning
confidence: 97%
“…Indeed, inhibition of fatty acid -oxidation with trimetazidine led to increased glucose oxidation, coupled with increases in cardiac mechanical work despite no changes in oxygen consumption for both rat [2] and human hearts [3], suggesting more efficient ATP production. Given the relationship between oxygen consumption and coronary flow [4], substrate selection by the working heart may be dictated by the availability of oxygen and/or coronary flow. Hence, conditions such as compensated cardiac hypertrophy that are characterised by regions of tissue ischaemia within the myocardium [5] exhibit increased glucose oxidation and decreased fatty acid -oxidation [6].…”
Section: Introductionmentioning
confidence: 99%